Adaptacja jako twórcza praktyka w polskim teatrze współczesnym. Krystian Lupa – Krzysztof Warlikowski – teatr krytyczny - Alina Sordyl (Postscriptum Polonistyczne)
Adaptation of different literary texts is one of the important practices in Polish contemporary theatre after 1989. Adaptations are being undertaken by the creators of the authorial theatres, directors of the repertory theatres and young artists who began their professional career in the theatre in the late nineties and after a year 2000. The article discusses three different types of adaptory practices. Krystian Lupa's adaptations are a kind of creative dialogue with literature that becomes a base for individual and evolving esthetics of his own theatre. Krzysztof Warlikowski struggles with the tradition and exceeds it. Directors representing critical theatre use classical dramatical and epic texts to build a dialectical discourse with Polish “readymade world”.